PRAKTEK BETERNAK SEBAGAI MEDIA PEMBELAJARAN KARAKTER : ANALISIS KUALITATIF PENUMBUHAN SIKAP MANDIRi, TANGGUNGJAWAB DAN PERCAYA DIRI SISWA KELAS 4 SDIT ALAM NURUL ISLAM - Sunarsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is a crucial foundation in addressing moral degradation within the world of education. This study aims to identify the process of developing independence, responsibility, and self-confidence through the co-curricular activity of KUB chicken farming at SD IT Alam Nurul Islam. Using a descriptive qualitative method, data were collected through participant observation, in-depth interviews, and documentation involving 4th-grade elementary students. The data analysis techniques followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The results indicate that farming activities effectively foster student character through experiential learning. The character of responsibility was formed through the consistency of the daily duty roster; independence emerged as teacher supervision decreased by the fourth week; and self-confidence increased through the students' courage in overcoming sensory barriers (feelings of disgust and fear) when interacting with the animals. Furthermore, this activity stimulated critical thinking skills, empathy, and an entrepreneurial spirit. This study concludes that contextual learning based on farming activities is an effective instrument for internalizing character values in a real-world context, rather than just as a theory.